2006
DOI: 10.1111/j.1740-8261.2006.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Use of Radiography vs. Ultrasonography in the Investigation of Gastrointestinal Foreign Bodies in Small Animals

Abstract: A question frequently asked by clinicians who are treating small animals suspected of having gastrointestinal foreign bodies is whether one imaging test such as survey radiography or ultrasonography is sufficient to make the diagnosis. A study was undertaken to try and answer this question. Survey abdominal radiography and ultrasonography was performed on 16 small animals (11 dogs, five cats) with clinical signs of an obstruction because of a confirmed gastrointestinal foreign body. The majority of the foreign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 18 publications
4
72
0
6
Order By: Relevance
“…In this study, survey radiographs were adequate to confirm a diagnosis of gastrointestinal foreign body in the majority of cases (LFB 62 · 5%, NLFB 70 · 1%). While radiographs may fail to demonstrate radiolucent foreign bodies, they can reveal segmental dilation of intestines with fluid and or gas or disparate bowel populations; however, this is not pathognomonic for foreign body obstruction (Clark , Root & Lord , Gibbs & Pearson , Graham et al , McNeel & Riedesel , Tyrell & Beck , Sharma et al , Ciasca et al ). It is important to note that this study was not designed to assess the accuracy of radiography for detection of gastrointestinal foreign bodies, as all dogs included in this study had confirmed foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, survey radiographs were adequate to confirm a diagnosis of gastrointestinal foreign body in the majority of cases (LFB 62 · 5%, NLFB 70 · 1%). While radiographs may fail to demonstrate radiolucent foreign bodies, they can reveal segmental dilation of intestines with fluid and or gas or disparate bowel populations; however, this is not pathognomonic for foreign body obstruction (Clark , Root & Lord , Gibbs & Pearson , Graham et al , McNeel & Riedesel , Tyrell & Beck , Sharma et al , Ciasca et al ). It is important to note that this study was not designed to assess the accuracy of radiography for detection of gastrointestinal foreign bodies, as all dogs included in this study had confirmed foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal foreign bodies are a common diagnosis amongst dogs presenting for emergency veterinary care and yet they often represent a diagnostic challenge (Clark , Guilford 1996, Aronson et al , Tyrrell & Beck , Hayes , Sharma et al ). After ingestion, the onset of clinical signs can vary from hours to weeks (Capak et al , Gianella et al , Hayes ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of ultrasound (US) in identification of GI tract perforation and characterization of pneumoperitoneum have also been described . Multiple veterinary studies have shown that abdominal ultrasonography improves detection of GI foreign bodies and has improved accuracy for the diagnosis of mechanical ileus when survey radiographic results are equivocal . Furthermore, while routine ultrasonography is inferior in the detection of pneumoperitoneum when compared with radiography and computed tomography (CT) in people, the improved detection of small volumes of peritoneal free fluid is considered beneficial .…”
Section: Introductionmentioning
confidence: 99%
“…In dogs or cats with linear foreign bodies and an intestinal perforation, there also may be free abdominal fluid and gas within the abdominal cavity. 4 In a study 4 on dogs and cats in which the usefulness of abdominal radiography was compared with that of abdominal ultrasonography for the detection of gastrointestinal foreign bodies, foreign bodies were detected on abdominal ultrasonographic images of all 16 affected dogs and cats but were detected on abdominal radiographic images of only 9 of 16 dogs and cats. 2 The use of gastrointestinal contrast studies has been described if the radiographic findings are equivocal; however, if there is an undetected perforation, contrast agent may leak into the peritoneum.…”
Section: Commentsmentioning
confidence: 99%